Correlations between Structural and Hardness of Fe-50%Al Coating Prepared by Mechanical Alloying - Didik Aryanto; Toto Sudiro; Agus Sukarto Wismogroho (Prodi Teknik Mesin, 2019)
Fe-50%Al coatings were deposited on the surface of low-carbon steel using mechanical alloying technique at different milling times. The correlation between structure and hardness of coating before and after heat treatment was investigated. At the milling time of less than 180 min, the coating has an elongated lamellar structure. The size of elongated lamellar structure decreased with increasing milling times which led to an increase in the hardness value of coating. After heat treatment, the coating transformed to FeAl intermetallic phase with a denser structure and uniform in the composition. It affected the hardness of coating. The hardness value of all samples after heat treatment was higher than coating after milling. The hardness of coating was strongly influenced by the morphology and phase of coating.